Young driver risky behaviour and predictors of crash risk in Australia, New Zealand and Colombia: Same but different? - Scott-Parker, Bridie; Oviedo-Trespalacios, Oscar (Accident analysis and prevention, 2017)
•Independently of country, all groups of participants reported frequent speeding.•Young drivers in Colombia self-reported more risky behaviour than those in AU or NZ.•Key crash-reduction strategies must target handheld mobile phone usage and drink driving.•Multi-country investigations improve understanding of young driver risk factors. Young drivers remain overrepresented in road crashes around the world, with road injury the leading cause of death among adolescents. In addition, the majority of road traffic crashes, fatalities and injuries occur in low- and middle-income countries. All young drivers are at risk due to a breadth of age- and inexperience-related factors; however it is well recognised that young drivers may also intentionally engage in risky driving behaviours which increase their crash risk. The aim of this paper is to examine the self-reported risky driving behaviour of young drivers in Australia, New Zealand (high-income countries), and Colombia (middle-income country), and to explore the utility of a crash risk assessment model in these three countries. Young drivers aged 16–25 years completed the Behaviour of Young Novice Drivers Scale (BYNDS), in addition to self-reporting crash involvement and driving offences. A hierarchical segmentation analysis via decision trees was used to study the relationship between self-reported crashes and risky driving. Young drivers in Colombia reported more risky driving than young drivers in New Zealand, and considerably more risky driving than young drivers in Australia. Significant differences among and across countries in individual BYNDS items were found, and 23.5% of all participants reported they had been involved in a road crash. Handheld mobile phone usage was the strongest predictor of crashes, followed by driving after drinking alcohol, and carrying friends as passengers. Country of origin predicted mobile phone usage, with New Zealand and Colombia grouped in the same decision tree branch which implies no significant differences in the behaviour between these countries. Despite cultural differences in licensing programs and enforcement, young drivers reported engaging in a similar breadth of risky behaviours. Road crashes were explained by mobile phone usage, drink driving and driving with passengers, suggesting interventions should target these three risk factors. Whilst New Zealand and Australia have implemented graduated driver licensing programs, are geographical neighbours, and are high-income countries, the finding that behaviours of young drivers in New Zealand and Colombia were more similar than those of young drivers in New Zealand and Australia merits further investigation.